The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jcrs.2008.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Epi-laser in situ keratomileusis: Comparative evaluation of epithelial separation with 3 microkeratomes

Abstract: Mechanical separation of the epithelial sheet in epithelial laser in situ keratomileusis (epi-LASIK) was safe and reproducible with all evaluated microkeratomes. Immunohistochemistry and electron microscopy showed the cleavage plane in epi-LASIK was between the basal epithelium and the basement membrane at the level of the lamina lucida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…11,14 Different qualities of epithelial flaps prepared using different epikeratomes might be one of reasons for these results. 5,22,23 Although, theoretically, the epithelial flap made by the epikeratome should contain more viable epithelial cells than in flaps prepared using alcohol or another chemical agent, some studies have reported that the basement membrane was partially or totally lost after epi-LASIK treatment and that most basal cells in the epithelial flap appeared to be dead. 4,13,[24][25][26][27] Therefore, epithelial flap management by LED was investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Different qualities of epithelial flaps prepared using different epikeratomes might be one of reasons for these results. 5,22,23 Although, theoretically, the epithelial flap made by the epikeratome should contain more viable epithelial cells than in flaps prepared using alcohol or another chemical agent, some studies have reported that the basement membrane was partially or totally lost after epi-LASIK treatment and that most basal cells in the epithelial flap appeared to be dead. 4,13,[24][25][26][27] Therefore, epithelial flap management by LED was investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that compared with conventional laser-assisted subepithelial keratectomy (LASEK), in which an epithelial flap is created after the epithelium is exposed to an alcohol solution, cell viability of the epithelial sheet is better in epi-LASIK surgery, in which mechanical separation is performed with a microkeratome. The quality of the epithelial separation is crucial for the success of the procedure because stromal lacerations or remaining islands of basal epithelial cells would reduce the optical quality of the cornea after photoablation (22). …”
Section: Epithelial Laser In Situ Keratomileusis (Epi-lasik)mentioning
confidence: 99%
“…Epi‐LASIK is performed using a mechanical device or epikeratome with a blunt blade to produce a cleavage plane 19 at the level of the BM for the epithelial flap, with no use of alcohol or other chemical agents. However, it does require the use of a vacuum suction ring.…”
Section: Surface Ablation Techniquesmentioning
confidence: 99%